Using positive deviance to improve timely access in primary care - Tara Kiran; Sam Davie; MaryBeth DeRocher (BMJ Open Quality, 2021)
Background Improving timely access in primary care is a continued challenge in many countries. We used positive deviance to try and identify best practices for achieving timely access in our primary care organisation in Toronto, Canada.Methods Semistructured interviews were used to identify practice strategies used by physicians who successfully maintained a low third next available appointment (TNA) (positive deviants, n=6). We then conducted a cross-sectional survey to understand the prevalence of identified promising practices among all physicians (n=70) in the practice. We used χ2 testing to understand whether uptake of promising practices among survey respondents was different for those with a median TNA of 7 days or less vs a median TNA over 7 days.Results We identified seven promising practice strategies used by positive deviants: adjusting the appointment template based on demand; reviewing the appointment schedule in advance; max-packing of visits; using phone, email and secure messaging; customising care for complex patients; managing planned absences; and involving the interprofessional team. 65 of 70 physicians responded to the survey on promising practices. Uptake of the promising practices was variable among survey respondents. In general, we found no association between uptake of promising practices and median TNA. One exception was that those with a median TNA of 7 or less were more likely to review the schedule in advance to potentially mitigate a visit using phone/email (62% vs 31%, p=0.0159).Conclusion Promising practices used by a small group of physicians (‘positive deviants’) to maintain good access were generally not associated with timely access among a larger sample of physicians in the practice. Our findings highlight the difficulty of untangling physician practice style and its contribution to timely access in primary care.